High Resolution Crystal Structure of Human β-Glucuronidase Reveals Structural Basis of Lysosome Targeting - Hassan, Md. Imtaiyaz; Waheed, Abdul; Grubb, Jeffery H.; Klei, Herbert E.; Korolev, Sergey; Sly, William S. (PLOS ONE, 2013)
Human β-glucuronidase (GUS) cleaves β-D-glucuronic acid residues from the non-reducing termini of glycosaminoglycan and its deficiency leads to mucopolysaccharidosis type VII (MPSVII). Here we report a high resolution crystal structure of human GUS at 1.7 Å resolution and present an extensive analysis of the structural features, unifying recent findings in the field of lysosome targeting and glycosyl hydrolases. The structure revealed several new details including a new glycan chain at Asn272, in addition to that previously observed at Asn173, and coordination of the glycan chain at Asn173 with Lys197 of the lysosomal targeting motif which is essential for phosphotransferase recognition. Analysis of the high resolution structure not only provided new insights into the structural basis for lysosomal targeting but showed significant differences between human GUS, which is medically important in its own right, and E. coli GUS, which can be selectively inhibited in the human gut to prevent prodrug activation and is also widely used as a reporter gene by plant biologists. Despite these differences, both human and E. coli GUS share a high structure homology in all three domains with most of the glycosyl hydrolases, suggesting that they all evolved from a common ancestral gene.